ANALISIS PEMANFAATAN TEKNOLOGI INFORMASI TASPEN KEPADA PESERTA DI KANTOR PT. TASPEN (PERSERO) KANTOR CABANG KEPULAUAN NIAS - Zebua, Yunus Sarofati; Ndraha, Ayler Beniah; Zalukhu, Yuterlin; Mendrofa, Yupiter (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Abstract. Utilization of information technology is the behavior of technology employees with their duties, measurement, based on frequency of use in the diversity of applications used. Information technology is the study, design, development, implementation, support or management of computer-based information systems, especially software applications and computer hardware. Lack of use of information technology in the PT area. Taspen (Persero) Nias Islands Branch Office causes obstacles related to information, rights and obligations for Taspen participants, especially for participants who have entered the Retirement Age Limit. Because this obstacle often becomes a problem for a company, where when participants do not know their rights as Taspen participants, the company will be involved in the investigation process for Taspen participants who have obstacles or obstacles in managing their rights. This research aims to find out how information technology is used by participants at PT Taspen (Persero) Nias Islands Branch Office. Based on the research results, it was concluded that PT Taspen (Persero) Nias Islands Branch Office had taken significant steps in utilizing Information Technology (IT) to overcome the obstacles faced by retired participants, such as device non-uniformity, limited digital literacy, and electricity stability problems. However, there are still several challenges that need to be overcome. Improving participants' understanding of applications and web portals, as well as improvements in technical aspects and data security policies, is essential. Outreach and education are key in helping participants, especially older ones, understand the full benefits of IT in managing their retirement. Efforts to improve customer service with faster responses are also needed. With an ongoing commitment to increasing participants' technological understanding, improving the onboarding process, and maintaining strict data security standards, PT. Taspen (Persero) Nias Islands Branch Office can maximize the benefits of IT, provide a positive experience for participants, and maintain a high level of trust in the company.